A comparison between water circulation and terrestrially-driven dissolved silica fluxes to the Mediterranean Sea traced using radium isotopes. (1st October 2018) - Tamborski, Joseph; Bejannin, Simon; Garcia-Orellana, Jordi; Souhaut, Marc; Charbonnier, Céline; Anschutz, Pierre; Pujo-Pay, Mireille; Conan, Pascal; Crispi, Olivier; Monnin, Christophe; Stieglitz, Thomas; Rodellas, Valentí; et al.
Abstract: The circulation of seawater through permeable coastal sediments is increasingly recognized as an important source of nutrients, including dissolved silica (DSi), to the coastal ocean. Here, we utilized a Ra isotope ( 223 Ra, 224 Raex, 228 Ra) mass balance to quantify DSi fluxes driven by water circulation to a small shallow coastal lagoon (La Palme; French Mediterranean) during June 2016, as compared to karstic groundwater spring inputs. The DSi flux driven by lagoon water circulation (derived from 224 Raex ) was approximately one order of magnitude greater (1900 ± 1700 mol d −1 ) than the DSi load of the karstic groundwater spring (250 ± 50 mol d −1 ) and greater than molecular diffusion (970 ± 750 mol d −1 ). Lagoon water circulation was a negligible source of 228 Ra, indicating that circulation-driven DSi inputs occur over a time-scale of days. Offshore transects were studied to quantify fluxes of marine-derived submarine groundwater discharge (SGD) from the permeable sandy coastline adjacent to the lagoon, into the Mediterranean Sea. Surface water transects revealed near-shore enrichments of Ra and DSi, attributed to wave-setup and water exchange through the permeable beach between the lagoon and the sea. Upscaling over the 9.5 km stretch of sandy beaches results in a marine SGD-driven DSi flux of 2.3 ± 1.3 × 10 4  mol d −1, similar in magnitude to the Têt river during November 2016 (3.3 ± 2.4 × 10 4  mol d −1 ), the largest river in the region. A positive relationship between DSi and 224 Raex in lagoon water and seawater, but not 228 Ra, suggests that 224 Raex and DSi enrichments are derived from a similar source, the sediment (i.e. lithogenic particle dissolution), operating on short time-scales. A marine SGD-driven DSi flux to the Gulf of Lions (3.8 ± 2.2 × 10 5  mol d −1 ) is likely continuous over time. The relatively constant DSi inputs from water circulation for the shallow lagoons and beaches along the French Mediterranean Sea may sustain primary production in the coastal zone. In comparison, terrestrial groundwater and rivers supply temporally variable nutrient (N, P, Si) inputs via changes in regional precipitation, runoff and aquifer storage.